Summer and Winter Marine Heatwaves Favor an Invasive Over Native Seaweeds. Issue 6 (14th August 2020) - Atkinson, James; King, Nathan G.; Wilmes, Sophie B.; Moore, Pippa J.
Abstract : Marine heatwaves (MHWs) are emerging as forceful agents of ecosystem change and are increasing in frequency, duration, and intensity with climate change. During MHWs, physiological thresholds of native species may be exceeded while the performance of invasive species with warm affinities may be enhanced. As a consequence, MHWs could significantly alter an ecosystem's invasive dynamics, but such interactions are poorly understood. Following a 10‐d acclimation period, we investigated the physiological resistance and resilience of an intertidal rock pool assemblage invaded by the seaweed Sargassum muticum to realistic 14‐d marine heatwave scenarios (+1.5°C, +2.0°C, +3.5°C) followed by a 14‐d recovery period. We conducted mesocosm experiments in both summer and winter to investigate temporal variability of MHWs. MHW treatments had clear negative impacts on native seaweeds ( Fucus serratus and Chondrus crispus ) while enhancing the performance of S. muticum. This pattern was consistent across season indicating that acclimation to cooler ambient temperatures results in winter MHWs having significant impacts on native species. As climate warming advances, this may ultimately lead to changes in competitive interactions and potentially exclusion of native species, while invasive species may proliferate and become more conspicuous within temperate rocky shore environments.